Investigation of anomalous diffusion of aluminum into silicon - Alexey V. Bespalov; Mikhail S. Afanasyev; Olga L. Golikova; Igor A. Kharitonov; Alexandra A. Muravyeva (Безопасность информационных технологий, 2023)
The process of Al diffusion into silicon substrate of an integrated circuit is studied experimentally and theoretically in details in order to analyze the invariance of the diffusion mechanism according to the Arrhenius law. During the process of practical investigation of the aluminum admixture with silicon, the abnormal diffusion of Al in Si (uncontrolled and nonlinear) was observed. The results of this experimental study were obtained using the FIB stations HeliosNanoLab 400 and HeliosNanoLab 450F (hereinafter referred to as the Station). All five samples investigated were fragments of monocrystalline silicon wafers (CEF) with electronic conductivity, doped with phosphorus, with a thin layer of a silicon oxide (SiO2) as gate dielectric, grown on them by the oxidation method. Using the Station, 6 round holes with a diameter of about 5 microns were formed in all samples for the entire thickness of the dielectric. The electron beam method was used for metallization, an aluminum membrane with a thickness of about 200 nm was formed onto the samples. Annealing of the samples was carried out in vacuum at five different temperatures during 40 minutes time intervals. Cross-sections were produced using the Station and the annealing process was analyzed. The diffusion results were linear and controlled up to annealing temperature T=600°C. At the temperature higher than T=600°C, the diffusion mechanism has changed dramatically. The following explanation was proposed by us. The SiO2 dielectric was in a compression state, silicon and aluminum were in an extension state, and accelerated (abnormal) diffusion which was detected was associated with the mechanical stresses at the point of SiO2 and silicon contact. Such mechanical stresses can affect the reliability of the chips. A possible solution to this problem was proposed, namely to create an additional barrier layer with ~ 0.15 microns thickness between aluminum and monocrystalline silicon.